DIGITAL LITERACY SKILLS OF MECHANICAL ENGINEERING EDUCATION LECTURERS: A SYSTEMATIC LITERATURE REVIEW IN THE CONTEXT OF INDUSTRY 4.0 - Riyadi, Andrian; Muhtarom, Imam; Dewangga, Andrian Wisnu (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
The main issue is the gap in digital literacy competence among mechanical engineering education lecturers due to the lack of adequate training, support, and facilities from the institution. This research used a systematic literature review approach to identify the gaps in digital literacy among mechanical engineering education lecturers. A systematic literature review was conducted, starting with exploration, evaluation, and presentation of data from previous studies that discuss digital literacy competence for lecturers, especially in the context of mechanical engineering education. A total of 100 international articles published between 2018 and 2024 were reviewed based on keywords and research findings. After the review, 66 relevant international articles were identified and can be used as the foundation for this research. The results of the study show that digital literacy competencies for lecturers in mechanical engineering education are crucial in improving the quality of teaching and student competencies to face the challenges of Industry 4.0. Intensive and ongoing training programs can enhance lecturers' abilities to master technology, with the prospects of this research focusing on cybersecurity, digital ethics, and more structured training programs to support innovative mechanical engineering education, thus meeting the demands of the ever-evolving job market. This study contributes to the existing literature by providing a comprehensive synthesis of digital literacy challenges and potential solutions in mechanical engineering education, emphasizing the urgent need for structured and targeted training programs. The novelty of this research lies in its focus on identifying specific gaps in digital competencies within this discipline, highlighting key areas such as cybersecurity and digital ethics, which have been underexplored in previous studies.